Exploring Teachers' Perspectives on Attitude Change Instruction in Social Studies Education - Appiah-Kubi, Ebenezer; Bordoh, Anthony; Eshun, Isaac (Advances in Social Sciences Research Journal, 2024)
This qualitative study explores the perspectives of social studies teachers in Ghana on attitude change instruction within the context of senior high school. The study investigates teachers' viewpoints, experiences, and practices related to attitudinal change instruction in Social Studies education. The study adopted a multiple case study design to gain in-depth insights into teachers' perceptions of attitudinal instruction. The population comprises Social Studies teachers in public Senior High Schools in the Oforikrom Municipality and Sekyere South District of the Ashanti Region. Sampling techniques involve selecting participants from nine public Senior High/Technical and Vocational Schools in the study area. The main instrument for data collection was semi-structured interviews. The study highlights the complexities and opportunities in fostering positive attitudes and behaviours among Ghanaian Senior High School students. Conclusions drawn from the study inform recommendations for enhancing attitude change instruction in Social Studies education, emphasising the importance of teacher commitment, student engagement, and a supportive educational environment.